Effects of bariatric surgery on testosterone level and sexual function in men with obesity: A retrospective study - Chen, Guoji; Sun, Luping; Jiang, Shuwen; Chen, Xiaomei; Zhu, Jie; Zhao, Xin; Yu, Shuqing; Dong, Zhiyong; Chen, Yuan; Zhang, Wen; Yang, Wah; Wang, Cunchuan (Frontiers in Endocrinology, 2023)
Introduction: Bariatric surgeries induce well-documented weight loss and resolve obesity co-morbidities. Sexual function is one of the aspects of life quality and may benefit from surgery. Few studies have revealed the impact of bariatric surgeries on sexual function in Chinese males with obesity. Methods: This is a retrospective cohort study of patients undergoing bariatric surgery (laparoscopic sleeve gastrectomy, LSG, or laparoscopic Roux-en-Y gastric bypass, LRYGB). Data were collected between September, 2017 and February, 2022. International Index of Erectile Function (IIEF) questionnaire was used to evaluate: erectile function, intercourse satisfaction, orgasmic function, sexual desire and overall satisfaction. Sex hormones and other blood tests were evaluated before and no less than one year after the surgery. Results: Fifty-nine Chinese male patients completed the IIEF questionnaire. The multivariate logistic regression analysis revealed that BMI was the single independent risk factor of the severity of erectile dysfunction. Pre-operative testosterone levels had negative correlations with BMI and waist circumference. Thirty-seven patients completed the post-operative questionnaire with a mean follow-up of 23.2 months. Conclusion: BMI and waist circumference were negatively correlated with testosterone level. BMI was an independent risk factor for the severity of ED. LSG and LRYGB led to positive and sustained improvement in sexual function of males with obesity. The two procedures had a comparable effect, more objects being needed. Sex hormones level also could be reversible. But better weight loss effect did not predict the better change of sexual function. More BMI loss might predict more increase of testosterone.